ANALISIS DIMENSIONALITAS DATA MAGNETOTELURIK LAPANGAN PANAS BUMI â€œSAâ€ BERDASARKAN METODE TENSOR FASE - Akbar, Shofya; Setyawan, Agus; Yulianto, Tony; Baroek, Marino Christiano; Ramadhan, Irvan (BERKALA FISIKA, 2020)
Magnetotelluric (MT) method is one of a passive electromagnetic method in geophysics. Principally MT measures the temporal variation of the electromagnetic field that is induced to the surface of the earth to get the subsurface resistivity structure. Information about the geoelectric strike and dimensionality of the magnetotelluric data is important to modelling the subsurface structure. Information is used to determine the 1D, 2D or 3D approach that can be used to interpret MT data. Therefore, an aim of study is to identify the direction of the geoelectric strike and dimensionality structure in the "SA" geothermal field. The data were used is secondary data that has been corrected using shift correction. Phase tensor method was used to analysis the dimensionality of magnetotelluric data. Principally the phase tensor method is to determine the dimensionality by looking the difference between maximum and minimum phase that can be describe the main direction of structure in the field area. The results of geoelectric strike analysis and the dimensionality of the magnetotelluric field data for the "SA" geothermal field show the direction of geoelectric strike N345oE or N15oW with 1D, 2D and 3D dimensionality structures.